IMPACT OF ORAL ADMINISTRATION OF MAHAVATAVIDHWANSAN RASA ALONG WITH MAHANARAYAN TAILA KATIBASTI IN GRIDHRASI: A CASE REPORT - Goswami, Ditimoni (International Journal of Ayurveda and Pharma Research, 2015)
Gridhrasi is one of the commonest disorders found in clinical practice. Gridhrasi can be correlated with that of sciatica. Gridhrasi being a Vatavyadhi the general line for treatment of Vatavyadhi can be applied to it. Basti is considered as the treatment of choice in Vatavyadhi in Ayurvedic samhitas. Several oral medicinal preparations are also mentioned in the classics for the treatment of Gridhrasi. The disease ranges from simple backache to severe complications like deformities and ultimately cripples the patient. The allopathic system of medicine has conducted extensive studies on non-steroidal anti-inflammatory drugs, analgesics and other physiotherapies but could not find a suitable medication or technique which is safe and effective for Gridhrasi. In the present case study, Gridhrasi has been treated with oral administration of Mahavatavidhwansan rasa for thirty days along with Mahanarayan taila katibasti for 15 days. The clinical trial revealed that this Ayurvedic combination therapy significantly improved the Gridhrasi condition of the patient.